Acute Kidney Injury: Incidence And Mortality in Critically ill Neonates (Medical Forum Monthly, 2024)
Objective: To examine the incidence of acute kidney injury and associated mortality in neonates admitted in neonatal intensive care unit.Study Design: Prospective study.Place and Duration of Study: This study was conducted at the Department of Pediatrics, Niazi Medical College Sargodha from 1st July 2018 to 30th June 2019.Materials and Methods: Total 240 critically ill neonates of both gender admitted to NICU were analyzed in this study. Patients age from 2 to 30 days. Patients detailed history including age, sex and causes of admission to NICU were recorded after taking consent from patient’s parents and guardians. Serum creatinine >1.5mg/dl and BUN >20mg/dl on admission and at 24 hours was defined to have acute kidney injury. Risk factors of acute kidney injury and mortality rate were examined.Results: Twenty six (10.83%) patients had acute kidney injury, in which 18 (69.23%) patients were males while 8 (30.77%) were females with mean age 6.34±5.68 days. 16 (61.54%) patients were preterm and 10 (38.46%) were term neonates. 15 (57.69%) neonates had low birth weight while 11 (42.31%) had normal birth weight. The most common risk factor was sepsis found in 17 (65.38%) neonates followed by birth asphyxia 12 (46.15%) and shock in 7 (26.92%). All patients had one or more risk factors associated to AKI. Mortality rate was significantly high in patients with AKI as compared to patients with non-AKI 34.62% vs. 25 (11.68%).Conclusion: The incidence rate of acute kidney injury was high in critically ill neonates admitted to NICU. Mortality rate was also high in patients with AKI as compared to non-AKI patients.